IMPLEMENTATION OF REGISTRATION OF OWNERSHIP RIGHTS FOR JOINT ASSETS IN THE EAST LAMPUNG REGENCY LAND OFFICE - Reny Raymond Diaz (Cepalo, 2019)
Article 37 paragraph (1) PP 24 of 1997 states that the transfer of ownership rights over land can only be registered if proven by a PPAT deed. The PPAT Deed has the strength of perfect proof because it contains all elements of civil evidence so that it does not require other documents as a basis for registration of rights. This is confirmed by the Regulation of the Head of BPN Number 1 of 2010, in fact, the head of the land office does not necessarily want to accept the deed as the only proof of transfer to serve as the basis for registering the transfer of rights. The head of office requires the addition of documents in the form of a photocopy of a marriage book, a photocopy of a divorce certificate, marriage agreement, and / or a letter of approval from the heirs if one of the spouses has died. This study aims to determine the implementation of the transfer of ownership rights over joint property marriage. The research uses empirical normative juridical research methods. The research approach uses a statutory, analytical and participatory approach. Data analysis uses primary and secondary data to conclude using inductive logic. The results of the study show that: 1) the registration of the transfer of ownership of the joint property allows discretion because the laws governing it are incomplete and unclear. 2) Deed of PPAT has not been able to provide a guarantee of full legal certainty in land registration so that it still requires other documents as a complementary proof. 3) Efforts by the Land Office in providing guarantees of legal certainty of certificates are by applying additional document requirements in the registration of the transfer of ownership of shared assets.